2018
DOI: 10.1002/aoc.4245
|View full text |Cite
|
Sign up to set email alerts
|

Surface modified SPIONs‐Cr(VI) ions‐immobilized organic‐inorganic hybrid as a magnetically recyclable nanocatalyst for rapid synthesis of polyhydroquinolines under solvent‐free conditions at room temperature

Abstract: In this work, a magnetic hybrid dichromate nanocomposite with triphenylphosphine surface modified superparamagnetic iron oxide nanoparticles (SPIONs) as a recyclable nanocatalyst was designed, prepared and characterized by Fourier transform infrared spectroscopy (FT-IR) spectra, X-ray diffraction (XRD) pattern analysis, vibrating sample magnetometer (VSM) curves, X-ray fluorescence (XRF) analysis, thermogravimetric analysis (TGA), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Surface functionalization of magnetic nanoparticles (MNPs) is a well‐designed way to bridge the gap between heterogeneous and homogeneous catalysis. The introduction of MNPs in a variety of solid matrices allows the combination of well‐known procedures for catalyst heterogenization with techniques for magnetic separation . So, these types of catalysts play a vital role in approaching the green chemistry goal.…”
Section: Introductionmentioning
confidence: 99%
“…Surface functionalization of magnetic nanoparticles (MNPs) is a well‐designed way to bridge the gap between heterogeneous and homogeneous catalysis. The introduction of MNPs in a variety of solid matrices allows the combination of well‐known procedures for catalyst heterogenization with techniques for magnetic separation . So, these types of catalysts play a vital role in approaching the green chemistry goal.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate benefit of this work, our catalyst was compared with that used in other published methods . Some results for the reduction of MO and MB are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Separation of nanoparticles from the reaction medium using simple methods such as filtration and centrifugation is difficult . To overcome these difficulties, different solid supports such as TiO 2 , graphene, mesoporous materials, and Fe 3 O 4 were applied for the immobilization of metal nanoparticles and the construction of the heterogeneous nanocatalyst . Graphene oxide (GO) has been identified as a new group of interesting catalysts because of their unique properties such as good stability, large surface area, high mechanical strength, and good adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Maleki and his research team have reported the successful preparation of a magnetic dichromate hybrid with triphenylphosphine surface modified with superparamagnetic iron oxide nanoparticles (Scheme ) . The resulting nano‐composite (Fe 3 O 4 @SiO 2 @PPh 3 @Cr 2 O 7 2− ) was confirmed by a series of spectroscopy techniques such as FT‐IR, XRD, SEM, VSM, TGA, XRF, TEM and dynamic light scattering.…”
Section: Magnetically Recoverable Nanocatalysts In Synthesis Of Polyhmentioning
confidence: 99%
“…The resulting nano‐composite (Fe 3 O 4 @SiO 2 @PPh 3 @Cr 2 O 7 2− ) was confirmed by a series of spectroscopy techniques such as FT‐IR, XRD, SEM, VSM, TGA, XRF, TEM and dynamic light scattering. The SEM analysis demonstrated that the magnetite nanocatalyst particles are spherical with a mean diameter of 25 nm and with uniform size and good dispersity . The efficiency of the Fe 3 O 4 @SiO 2 @PPh 3 @Cr 2 O 7 2− as a magnetically recoverable catalyst was then evaluated in the synthesis of polyhydroquinolines via the four‐component reactions of various aldehydes, dimedone, ethyl acetoacetate and ammonium acetate under solvent‐free conditions at room temperature (Scheme ).…”
Section: Magnetically Recoverable Nanocatalysts In Synthesis Of Polyhmentioning
confidence: 99%